The association between atopic dermatitis and serum 25‐hydroxyvitamin D in children: Influence of sun exposure, diet, and atopy features—A cross‐sectional study. Issue 2 (29th January 2020) - Sanmartin, Rosalía; Pardos, Carlos; Doste, Divina; Aguilera, Jose; Alijarde, Roberto; Jesús Agón‐Banzo, Pedro; García‐Malinis, Ana Julia; Puzo, José; Hernández‐Martín, Ángela; Gilaberte, Yolanda
Abstract: Background: Previous studies have linked low serum vitamin D (VD) or 25‐hydroxyvitamin D (25(OH)D) levels with increased severity of atopic dermatitis (AD) in children. Objective: To investigate the association between serum VD (25(OH)D) levels and AD and AD severity, considering the influence of diet and sun exposure. Methods: We performed a prospective cross‐sectional study of healthy controls and children diagnosed with AD. Participants were recruited between January 2011 and December 2012, and the following parameters were assessed: age, sex, body mass index (BMI), AD severity, Fitzpatrick skin type, asthma and rhinitis history, dietary VD intake, daily potential sun‐induced VD production, sunscreen use, 25(OH)D and IgE serum levels, and results of the ImmunoCAP Phadiatop Infant test. Results: The study population consisted of 105 healthy controls and 134 AD patients. Serum 25(OH)D levels were significantly lower in moderate and severe AD than in mild AD, although this association was only significant for patients with light Fitzpatrick skin type (mean(SD) 36.7 (11.9) ng/mL; moderate 28.8 [11.5] ng/mL; and severe 27.6 [12.1] ng/mL, P  = .045). Logistic regression analysis revealed a positive association between severe AD and both positive ImmunoCAP Phadiatop test and BMI. Conclusion: Our data support an association between VD deficiency and AD severity only in patients with light complexion.